Iliá Yefimovich Repin - Tejedor Estupiñan, Ricardo Alonso (Universidad Pedagógica y Tecnológica de Colombia, 2018)
He was born on August 5, 1844 in the small Ukrainian town of Chuguev. Son of a settler farmer and ex-military, and like many sons of military colonists, went to the academy of topography of the military school, where he arose his passion for drawing, painting and sculpture. At the age of thirteen he demonstrated his ability to make portraits and devoted himself to making religious icons and restorations for the Orthodox churches of his people, under the teaching of iconographer Bunakov.